The Impact of Consumers’ Choice Deferral Behavior on Their Intertemporal Choice Preference - He-Lin Wei; Chen-Ying Hai; Shao-Ying Zhu; Bei Lyu; Bei Lyu; Bei Lyu; Bei Lyu (Frontiers in Psychology, 2021)
The purpose of this study is to explore the influence of consumers’ choice deferral behavior on their intertemporal choice preference. The empirical study shows that consumers’ choice deferral behavior can significantly affect their intertemporal decision preference through the level of hopefulness. Compared with non-choice deferral behavior, choice deferral behavior can improve the level of consumers’ sense of hopefulness, which then makes them prefer larger-longer interests in intertemporal decision-making. The effect of consumers’ sense of hopefulness on their intertemporal choice preference is moderated by their perceived information integrity. When the perceived information integrity is low, the effect of hopefulness on intertemporal decision preference will be enhanced, but when the perceived information integrity is high, the effect of hopefulness on intertemporal decision preference will not be affected. In addition, the theoretical and practical significance of this study and the prospect of future research are also discussed.